Mengapa Siswa Takut Berbicara - Ismarani Fikri Arifah; Indriyani Saputri; Rahmad Alrian (Jurnal Pendidikan Dirgantara, 2025)
Speaking anxiety among students is a common phenomenon that affects their academic performance and personal development. This study aims to explore the reasons behind students' fear of speaking in various educational settings. Using a literature review method, this research examines previous studies related to psychological, social, and educational factors contributing to students’ reluctance to speak. The findings indicate that speaking anxiety is primarily caused by fear of making mistakes, low self-confidence, and negative social evaluations from peers or teachers. Additionally, classroom environment, teaching methods, and cultural influences also play a significant role in shaping students' willingness to speak. The impact of this fear extends beyond academic performance, affecting students' participation, self-expression, and future communication skills. Several strategies have been identified to reduce speaking anxiety, including fostering a supportive learning environment, encouraging positive reinforcement, and implementing interactive teaching methods. Educators are encouraged to create a more inclusive atmosphere that minimizes students' fear of judgment and enhances their confidence in speaking. This study contributes to the existing body of knowledge on students' speaking anxiety by summarizing key factors and offering practical implications for teachers, educators, and policymakers. Future research could further explore intervention programs that effectively address students' fear of speaking in different cultural and educational contexts.